The Effect of Gym Ball Exercise During Pregnancy on Accelerating the Perinatal Process at the Nur Kholidah Pulungan Clinic - Ashari, Maya (Cattleya Darmaya Fortuna, 2025)
Gym ballis a physical therapy ball that can help mothers in the first stage of labor in the progress of their labor. Gym Ball is a physiotherapy ball that helps mothers in the first stage of labor and can be used in various positions. The elasticity and curvature of the ball stimulates receptors in the pelvis, so that by applying gravity while increasing the release of endorphins, the movement of sitting on the ball and stones provides a feeling of comfort and encourages the progress of labor, which is a sample of pregnant women as many as 30 respondents. From the results of the study showed that the distribution of gym ball exercise and acceleration of the labor process about gym ball exercise at the nurkholidah pulungan clinic in 2025. With respondents as many as 30 respondents, it was found that, the majority who participated in gym ball exercise were 24 respondents (80%) and those who did not participate in gym ball exercise were 6 respondents (20%), while those who were fast in accelerating the labor process were 27 respondents (90%) and those who were slow in accelerating the labor process were 3 respondents (10%). The results of bivariate analysis using the chi-square test on gym ball exercise and the acceleration of the labor process in the influence of gym ball exercise during pregnancy on the acceleration of the labor process obtained a value of p = 0.005 (p <0.05) so there is a significant influence between gym ball exercise and the acceleration of the labor process. It can be concluded that there is a significant influence between gym ball and the acceleration of the labor process about gym ball exercise at the Nurkholidah Pulungan clinic. It is recommended that mothers participate more often in gym ball exercise in accelerating the labor process to make it easier to undergo the labor process.